Strong Citizenship Promotion through A Perspective of New Public Governance - Pearnpitak, Kittipong (King Prajadhipok’s Institute Journal, 2024)
This study aimed to propose a critical analysis of strong citizenship emergence along with a guideline to drive strong citizens in Thailand. This study was based on New Public Governance (NPG) that covers Intergovernmental Management (IGM) using the concept of Collaborative Governance (CG) to analyze the causes and conditions of strong citizenship from the example in Golden Gate National Park that reflected the mechanism of network power in various dimensions. It started with leaders facing problems to change a crisis into an opportunity for co-development of the space. However, the representation of the common issue of network power could be described under “New Strong Citizen Power” to illustrate the movement by changing the main actors or the public sector into the people sector. Ultimately, the key concept was to find common ground for development based on the role that one can perform as the basis for a change of mind to become a strong citizen who plays a significant role in the development of Thailand in the global society.